Phosphorylation and ubiquitination of the IκB kinase complex by two distinct signaling pathways - Shambharkar, Prashant B (Nature Publishing Group, 2007)
The IκB kinase (IKK) complex serves as the master regulator for the activation of NF-κB by various stimuli. It contains two catalytic subunits, IKKα and IKKβ, and a regulatory subunit, IKKγ/NEMO. The activation of IKK complex is dependent on the phosphorylation of IKKα/β at its activation loop and the K63-linked ubiquitination of NEMO. However, the molecular mechanism by which these inducible modifications occur remains undefined. Here, we demonstrate that CARMA1, a key scaffold molecule, is essential to regulate NEMO ubiquitination upon T-cell receptor (TCR) stimulation. However, the phosphorylation of IKKα/β activation loop is independent of CARMA1 or NEMO ubiquitination. Further, we provide evidence that TAK1 is activated and recruited to the synapses in a CARMA1-independent manner and mediate IKKα/β phosphorylation. Thus, our study provides the biochemical and genetic evidence that phosphorylation of IKKα/β and ubiquitination of NEMO are regulated by two distinct pathways upon TCR stimulation.